(3CUhd Gdabgs - (3GdMSjfj GdMdj, GdYejOj, YejO GdOjf, GdCYQL, YHO GdeWdH Hf eMeO Hf Ydj, J (B745 (3g`s
(3ChdgG (B:s
... (3CbSGeG CNQi GfaSe EdjgG HGdfXQ Edi GYJHGQ (B... (3hGdZGjI HGbj PcQgG EPG JbQQ gPG aGYde Cf GdbGFdjf Hchf GdbjGS MLg EPG SHb Edi Cf GdefGSHI hGdGYJHGQ jOd Ydi chf Pdc GdhUa (B...s
(3BNQgG (B:s
... (3Ydi Cfg dG jeJfY JYdjd GdMce HYdJjf ceG SHb GdHMK ajg hgPG aEfG dh bdOfG GfaQGO eG PcQ GdeSJOd eLQOG Yf GdeYGQV UM chfg YdI ELeGYG hEfeG UM GdJYdjd Hg UM dchfg UGdMG dPdc (B...s
(3JHUQI GdYfhGf (B:s
(3efjI GddHjH aj TQM GdJgPjH (B- (3Cj JgPjH WQjb GdhUhd Edi Yde GdCUhd GdePchQ aj (B( (3GdPQjYI L (B4 (3` U (B511 ) (3ddYdGeI GdMdjs
(3JHUQI GdeDda (B:s
(3GHf CNJ GdYdGeI GdMdj hJdejPgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B2/314s
Keywords: (3abg GdePGgH GdCNQis